Phase Change Material (PCM) Microcapsules for Thermal Energy Storage - Guangjian Peng; Guijing Dou; Yahao Hu; Yiheng Sun; Zhitong Chen (Advances in Polymer Technology)
Phase change materials (PCMs) are gaining increasing attention and becoming popular in the thermal energy storage field. Microcapsules enhance thermal and mechanical performance of PCMs used in thermal energy storage by increasing the heat transfer area and preventing the leakage of melting materials. Nowadays, a large number of studies about PCM microcapsules have been published to elaborate their benefits in energy systems. In this paper, a comprehensive review has been carried out on PCM microcapsules for thermal energy storage. Five aspects have been discussed in this review: classification of PCMs, encapsulation shell materials, microencapsulation techniques, PCM microcapsules’ characterizations, and thermal applications. This review aims to help the researchers from various fields better understand PCM microcapsules and provide critical guidance for utilizing this technology for future thermal energy storage.